Arranjos ocupacionais na aposentadoria de idosos saudáveis - Cecilia Melo Neves Xavier (2013)
Due to accelerated aging and increased life expectancy, retired people have been presenting conditions for engaging in activities for over 20 or 30 years more. With this in mind, retired people will need to come up with new occupational arrangements for their lives without work throughout that time. It is known that the need to be active is vital and that makes occupation play a central role in life. Work is one of these occupations and it gets special attention during adulthood. It functions as a key regulatory activity of daily life and it usually fills much of everyday productive hours, being responsible for developing skills and generating social recognition. To break away with it entails the need of reorganizing the set of occupations that bring meaning to life, based on the increasing amount of spare time. There is large a gap on this theme's literature on understanding this organization process, in what concerns the way individuals will access the occupations that will constitute this new routine. The aim of this work is to understand and discuss, from the perception of the retired elderly, how the occupations performed in the course of life play a role in the reorganization of occupations in the retirement process. This is a qualitative study using semi-structured interviews, whose life span paradigm was used as a theoretical anchor, because it has premises in line with the object of study. Development is perceived as a continuous and heterogeneous process that is contextualized to the experienced circumstances in one's subjective story. Of the interviews that were carried out, four categories emerged: for life; old ways, new occupations: now I can, other possibilities: the discovery. Results revealed that occupations performed in the course of life become meaningful references during retirement. In the first three categories respondents indicated a sense of continuity experienced in different ways, whether by the practice of the same occupations, including those retrieved after a gap, or of more enduring meanings. Occupation's linear continuity is found only in the first category. It is the permanence of the occupation itself in a more clear way. In contrast, in the second category the continuity is expressed by the prevalence of meaning, and in the third category, in the retrieving of an interrupted occupation. The emergence of new occupations practice were also detected, some which never before performed, proving that this moment can also be seen as a starting time. The changes that occur in occupational arrangements from the breach with work can bring other interests and possibilities of previously not performed or imagined occupations. By studying retirement, it was found that the retired person may find himself/herself in full development by continuing to perform their ongoing occupations or learning new ones.